Electrospun Nanofibers for Energy and Environmental Applications - Ding, Bin.; Ding, Bin.; Yu, Jianyong.; Yu, Jianyong. (Nanostructure Science and Technology,, 2014)
This book offers a comprehensive review of the latest advances in developing functional electrospun nanofibers for energy and environmental applications, which include fuel cells, lithium-ion batteries, solar cells, supercapacitors, energy storage materials, sensors, filtration materials, protective clothing, catalysis, structurally-colored fibers, oil spill cleanup, self-cleaning materials, adsorbents, and electromagnetic shielding. This book is aimed at both newcomers and experienced researchers in the field of nanomaterials, especially those who are interested in addressing energy-related and environmental problems with the help of electrospun nanofibers. Bin Ding, PhD, and Jianyong Yu, PhD, are both Professors at the College of Materials Science and Engineering, Donghua University, China.